Peran PKBM dalam Peningkatan Pertumbuhan Ekonomi dan Kesejahteraan Hidup Masyarakat Sesuai Target SDGs - Alim Harun Pamungkas; Vevi Sunarti; Wendi Ahmad Wahyudi (Universitas Negeri Padang, 2018)
Efforts to achieve sustainable development targets provide opportunities for various non-school education service programs such as those organized by PKBM. The non-formal education program held was based on counseling, training and mentoring programs. The program is used to assist in solving problems that arise in the application of innovation in the community. This study uses a qualitative approach with case study design. The results showed that the economic growth program was in the form of training programs and literacy learning to the community oriented to increasing productivity, investment, expanding opportunities and absorption of labor, reducing unemployment, disseminating innovation through the capacity to support science and technology, and increasing competitiveness.Keywords: PKBM, Economic Growth, Welfare, SDG’s